Deep disposal a documentary account of burying nuclear waste in Canada - Leiss, William 1939- (McGill-Queen’s University Press, 2024)
"Canada is one of many countries around the world that use nuclear reactors to generate electrical power, in part as of now to reduce our carbon footprint. Yet this energy produces hazardous, long-lived waste that emits dangerous radioactivity for tens of thousands of years. Nuclear waste, stored temporarily for decades, must be safely disposed so it will not pose a serious threat to human health and the environment. This means locations deep underground in granite, sedimentary rock, or clay. Canada’s ideal location is somewhere on the Canadian Shield, the 2.5-billion-year-old crystalline rock that undergirds much of the country. In 2010 several municipalities, most in Ontario, were asked to host the repository. In Deep Disposal William Leiss explains the challenges that have prevented this initiative from succeeding and why we must rethink the process for locating a site. High-level nuclear waste is the most hazardous byproduct of an energy source that is incredibly useful and increasingly in demand. Finding the ideal place to store it permanently is an urgent policy crisis facing our country. Deep Disposal reveals the nature of this crisis and how we might overcome it."--
Keywords: Radioactive waste disposal in the ground / Case studies; Radioactive waste disposal in the ground / Canadian Shield; Radioactive waste disposal in the ground / Government policy / Canada; Déchets radioactifs / Élimination dans le sol / Études de cas; Déchets radioactifs / Élimination dans le sol / Bouclier canadien; Déchets radioactifs / Élimination dans le sol / Politique gouvernementale / Canada